m⁶(m³+1) = 36
Let p = m³
Therefore;
m⁶ = m³*m³ = p*p = p²
It implies;
p²(p+1) = 36
p³+p² = 36
Using Substitution Approach (Substituting prime factor of 36 only in the equation 'p³+p² = 36' to get p).
The prime factors of 36 = 2 and 3.
For p = 2
Therefore;
2³+2² ≠ 36 but 12, p ≠ 2
For p = 3
Therefore;
3³+3² = 36
It implies;
p = 3
And
p = m³
Therefore;
m³ = 3
m = (3)^(⅓)
Or
m = crt(3)
Checking accuracy.
((crt(3)))⁹+((crt(3)))⁶
= (3)^(9/3)+(3)^(6/3)
= 3³+3²
= 27+9
= 36
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support